Corrigendum to “Study of Risk Factors Effects Recurrence of Lumbar Disc Herniation (LDH) after Open Spine Surgery” [Novelty in Biomedicine, Vol. 10 No. 1 (2022), Page 12-16] (https://doi.org/10.22037/nbm.v10i1.34872) - Goudarzi, Mehdi (Novelty in Biomedicine, 2022)
The authors regret that in the published version of the above-mentioned paper we have wrongly entered the affiliation (1). The correct first affiliation is "Medicine Faculty, Yazd Branch, Islamic Azad University, Yazd, Iran". The authors would like to apologize for any inconvenience caused.